Penerapan Metode Mind Mapping untuk Meningkatkan hasil belajar Siswa dalam Pembelajaran PAI di SMP Amal Mulya Tawangmangu Tahun Ajaran 2022/2023 - Hidayati, Warih Nurul (Peneliti.net, 2023)
The purpose of this study is to discuss 1) The application of learning using the mind mapping method in improving student learning outcomes in PAI learning at Amal Mulya Tawangmangu Middle School in the 2022/2023 Academic Year. 2) The inhibiting factors of students towards the implementation of learning using the mind mapping method in PAI learning at Amal Mulya Tawangmangu Middle School in the 2022/2023 Academic Year. This research is a qualitative research using descriptive method. To collect the required data is done by using data collection instruments through observation, interviews, and documentation. The subjects in this study were PAI teachers and the informants in this study were school principals. The data analysis techniques in this study used data collection, data reduction, data presentation, and drawing conclusions. Based on the results of this study, it was found that 1) Application of learning using the mind mapping method in improving student learning outcomes in PAI learning at Amal Mulya Tawangmangu Middle School in the 2022/2023 Academic Year. The results of direct observation or observation in the learning process carried out by researchers in the field show that Amal Mulya Tawangmangu Middle School has not yet applied the mind mapping method in PAI learning. Therefore the researchers tried to apply PAI learning using the mind mapping method in class VII, including: a) The condition of the students at the beginning of learning after the mind mapping method was applied to PAI lessons, the learning outcomes of students were equivalent to the previous method, b) Understanding still not good at applying the mind mapping method and PAI teachers are used to using the lecture method and using blackboards and markers in explaining it. 2) The inhibiting factors of students towards the implementation of learning using the mind mapping method in PAI learning at Amal Mulya Tawangmangu Middle School for the 2022/2023 Academic Year include: a) Students are less interested in PAI subjects, b) Lack of student motivation to learn, and c) each students have different absorption abilities.